الرسوم المتحركة التجريبية و أهم روادها - فارس قره بيت (Tishreen University, 2016)
يرصد البحث تاريخياً البداية الحقيقية لأفلام الرسوم المتحركة التجريبية و أهم اتجاهاتها ، كما يستعرض البحث أهم الرواد الذين أسهموا في انطلاقة الرسوم المتحركة التجريبية التجريدية في أوروبا و الولايات المتحدة الأمريكية ؛أمثال ليوبولد سوريفاج و فايكنغ إيغلنغ و هانز ريشتر... و أهم الأعمال و التقنيات التي قدموها ، ثم ينتقل البحث بعد ذلك إلى أهم رواد المدرسة التصويرية (التشخيصية ) في أوروبا أمثال لوت رينيغر و بيرتولد بارتوش و ألكسندر ألكسييف . ثم ينتقل البحث بعد ذلك و يستعرض الاتجاه التجريبي المعاصر الذي بدأ في خمسينات القرن الماضي ولا يزال مستمراً حتى وقتنا الحاضر ، حيث قدم هذا الاتجاه تجارب و أسماء مهمة و مفصلية في تاريخ الرسوم المتحركة ؛ أمثال والت ديزني و إيفان فانو و أوسامو تيزوكا ونورمان ماكلارن و جون هالاس ، و الذين حددوا مستقبل الرسوم المتحركة ، حيث أضاء البحث على أهمية كل من التجارب السابقة و التوجه المستقبلي لأفلام الرسوم المتحركة . This research investigates the actual beginning of experimental animation films and their main directions. The research also reviews the most important pioneers of abstract experimental animation in both Europe and the U. S. A. such as Leopold Survage, Viking Eggeling and Hans Richter, on the one hand, and the most important film productions and the techniques used, on the other. We move on after that to the most wellknown figures of the pictorial school in Europe as Lotte Reinger, Berthold Bartosch and Alexander Alexeieff. The research moves on to take up the review of the contemporary experimental directions which began in the early 1950's and continued up to the present time, the directions which produced significant figures and experiments of paramount importance in the history of animation , such as Walter Disney, Ivan Vano, Osamo Tezuka, Norma Mclaren in addition to John Halas. These approaches shape the future of animation. The present research sheds light on the significance of both previous (earlier) experiments and the prospect of animation films.